Competing Chinese Names for God: The Chinese Term Question and Its Influence upon Korea - Oak, Sung-Deuk (Journal of Korean religions, 2012)
This paper discusses the theological discourses of Roman Catholicism and Protestantism on the Chinese terms for God and their influence upon the term question in Korea. The term question in China is important to Korea, not only because the former became the linguistic and theological background of the latter in Sino-centric East Asian culture, and because all Chinese terms were imported to Korea and had competed with Korean Protestant terms, but also because theologies and discourses developed in China were used in the controversy in Korea. The paper discusses four groups: Roman Catholics in the seventeenth and eighteenth centuries (the Shangdi-Tianzhu Camp and the Tianzhu Camp), British and American Protestants (the Shangdi Camp and the Shen Camp), British Anglicans (the Tianzhu Camp), and Scottish Presbyterians (the Shangdi-Hananim Camp) in the nineteenth century.